Human papilloma virus (HPV) mediated cancers: an insightful update - Sadaf Khursheed Baba; Shahad Shahdad Eissa Alblooshi; Reem Yaqoob; Shalini Behl; Mansour Al Saleem; Emad A. Rakha; Fayaz Malik; Mayank Singh; Muzafar A. Macha; Mohammed Kalim Akhtar; Walid A. Houry; Ajaz A. Bhat; et al. (Journal of Translational Medicine)
Abstract Human papillomavirus (HPV), a DNA virus, is a well-documented causative agent of several cancers, including cervical, vulvar, vaginal, penile, anal, and head & neck cancers. Major factors contributing to HPV-related cancers include persistent infection and the oncogenic potential of particular HPV genotypes. High-risk HPV strains, particularly HPV-16 and HPV-18, are responsible for over 70% of cervical cancer cases worldwide, as well as a significant proportion of other genital and head and neck cancers. At the molecular level, the oncogenic activity of these viruses is driven by the overexpression of E6 and E7 oncoproteins. These oncoproteins dysregulate the cell cycle, inhibit apoptosis, and promote the accumulation of DNA damage, ultimately transforming normal cells into cancerous ones. This review aims to provide a comprehensive overview of the recent advances in HPV-related cancer biology and epidemiology. The review highlights the molecular pathways of HPV-driven carcinogenesis, focusing on the role of viral oncoproteins in altering host cell targets and disrupting cellular signalling pathways. The review explores the therapeutic potential of these viral proteins, and discusses current diagnostic and treatment strategies for HPV-associated cancers. Furthermore, the review highlights the critical role of HPV in the development of various malignancies, emphasizing the persistent challenges in combating these cancers despite advancements in vaccination and therapeutic strategies. We also emphasize recent breakthroughs in utilizing biomarkers to monitor cancer therapy responses, such as mRNAs, miRNAs, lncRNAs, proteins, and genetic markers. We hope this review will serve as a valuable resource for researchers working on HPV, providing insights that can guide future investigations into this complex virus, which continues to be a major contributor to global morbidity and mortality.